SLC6A3 and body mass index in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial - Hayes Richard B; Kvale Paul; Yeager Meredith; Chatterjee Nilanjan; Wang Sophia S; Bergen Andrew W; Morton Lindsay M; Azzato Elizabeth M; Chanock Stephen J; Caporaso Neil E (BMC, 2009)
Abstract Background To investigate the contribution of the dopamine transporter to dopaminergic reward-related behaviors and anthropometry, we evaluated associations between polymorphisms at the dopamine transporter gene(SLC6A3) and body mass index (BMI), among participants in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. Methods Four polymorphisms (rs6350, rs6413429, rs6347 and the 3' variable number of tandem repeat (3' VNTR) polymorphism) at the SLC6A3 gene were genotyped in 2,364 participants selected from the screening arm of PLCO randomly within strata of sex, age and smoking history. Height and weight at ages 20 and 50 years and baseline were assessed by questionnaire. BMI was calculated and categorized as underweight, normal, overweight and obese (<18.5, 18.5-24.9, 25.0-29.9, or ≥ 30 kg/m2, respectively). Odds ratios (ORs) and 95% confidence intervals (CIs) of SLC6A3 genotypes and haplotypes were computed using conditional logistic regression. Results Compared with individuals having a normal BMI, obese individuals at the time of the baseline study questionnaire were less likely to possess the 3' VNTR variant allele with 9 copies of the repeated sequence in a dose-dependent model (** is referent; OR*9 = 0.80, OR99 = 0.47, ptrend = 0.005). Compared with individuals having a normal BMI at age 50, overweight individuals (A-C-G-* is referent; ORA-C-G-9 = 0.80, 95% CI 0.65-0.99, p = 0.04) and obese individuals (A-C-G-* is referent; ORA-C-G-9 = 0.70, 95% CI 0.49-0.99, p = 0.04) were less likely to possess the haplotype with the 3'variant allele (A-C-G-9). Conclusion Our results support a role of genetic variation at the dopamine transporter gene, SLC6A3, as a modifier of BMI.